Detection of biofilm formation in clinical isolates of Streptococcus pneumoniae in Sanglah General Hospital, Bali, Indonesia - I Made Sathya Vijayananda; Made Agus Hendrayana; I Dewa Made Sukrama; Ni Nengah Dwi Fatmawati (Intisari Sains Medis, 2021)
Background: Streptococcus pneumoniae causes broad-spectrum infections from mild to severe with high morbidity and mortality rates in almost all of the world, namely pneumonia and meningitis. This bacterium has virulence factors that help their survival, one of which is biofilms. Biofilms help Streptococcus pneumoniae become resistant to antibiotics; thus, treating infections caused by these bacteria is difficult to treat. This study aims to determine the biofilm production ability of Streptococcus pneumoniae isolated from the Clinical Microbiology Laboratory of Sanglah General Hospital, Denpasar, Bali, Indonesia using the tissue culture plate method.Methods: The research design used was a descriptive observational study with cross sectional type. The clinical isolate of Streptococcus pneumoniae was isolated from the Clinical Microbiology Laboratory of Sanglah General Hospital. Biofilm formation was measured by the tissue culture plate method and carried out at the Microbiology Laboratory of the Faculty of Medicine, Udayana University. Data were analyzed using SPSS version 20 for Windows.Results: Most of the specimens were collected from blood (59.37%), followed by sputum (31.25%), and others (9.38%). It was found that 1 of 32 (3.10%) clinical isolates could form a biofilm with a strong formation category (the optical density value> 0.38). In contrast, the rest did not form biofilms with an optical density value of ?0.095.Conclusions: Not all clinical isolates of Streptococcus pneumoniae isolated from the Clinical Microbiology Laboratory of Sanglah General Hospital Denpasar were able to form biofilms, suggesting that other virulence factors also play a role in pneumococcal infection. However, a molecular approach is necessary for the detection of genes encoding biofilm-producing isolates in future studies.